Mechanical and durability properties of high performance 100 MPA rice husk ash concrete / Syamsul Bahri - Syamsul , Bahri (2017)
This thesis deals with the development of high performance concrete (HPC) of 100 MPa incorporating rice husk ash (RHA) as a supplementary cementing material (SCM). Some constraints to produce HPC of 100 MPa incorporating RHA are related to appropriate average particle size of RHA to be used, percentage replacement of cement with RHA at low water to binder ratio (w/b) concrete, mixing method and to design such HPC. Most information available on the strength of RHA concrete is up to compressive strength of 80 MPa only. In this study, three average particle sizes of RHA of 13.5, 20.43 and 29.92 μm were used in mortar mixes to find a suitable particle size to produce the highest compressive strength. In producing HPC, the homogeneity of mixing affects the mechanical properties of concrete. Conventional and two steps mixing method were examined in order to find which appropriate mixing method is more suitable. For 100 MPa HPC, the average particle size of RHA and suitable mixing method are 13.5 μm and the two step mixing method, respectively. This particle size and mixing method significantly improved the compressive strength of RHA concrete. Furthermore, the models based on five key factors, which are ratio of water to cement, binder content, percentages replacement of cement with RHA, ratio of fine aggregate to total aggregate and dosage of superplasticizer, were developed to design HPC containing RHA. The models were able to predict the value of slump as well as compressive strength at 1 day and 28 days. The optimum mix proportion of HPC of 100 MPa containing RHA was used for further study and compared with silica fume and OPC concretes. The fresh HPC was tested for slump, unit weight and air content. The hardened HPC was tested for compressive, tensile s, flexural strengths, modulus of elasticity and ultrasonic pulse velocity. The effect of water curing and air drying on compressive strength of the HPC were also studied. In durability tests, samples were tested for water absorption, total porosity, sorptivity, initial surface absorption and magnesium sulphate attack on compressive strength of HPC. The time dependent deformation tests such as drying shrinkage and restrained shrinkage at early age were also conducted. Test results revealed that the mechanical and durability properties of HPC incorporating RHA were better than that of control concrete. The compressive strength and ultrasonic pulse velocity increased, whereas the water absorption and total porosity decreased with w/b of 0.25 and the percentages of cement replacement with RHA up to 20%. HPC incorporating RHA is less sensitive to curing as insignificant differences in compressive strength were observed. The RHA and silica fume were able to function as a filler and pozzolanic material so that the porosity and water absorption of these concrete decreased due to the concrete being less porous and denser. In general, these concretes indicated good durability. The HPC containing 10% RHA showed better compressive strength than HPC containing 10% silica fume or OPC. Another advantage of utilizing 10% RHA instead of 10% silica fume in HPC is its ability to delay the propagation of cracks under restrained shrinkage at early ages. RHA, therefore, has the potential for contributing to the sustainable development and economic prosperity of the construction and agricultural industries of Malaysia as well as other rice growing countries of the world.